„Parade of flee“ and unhappened occupation of Klaipėda in 1938. Unknows pages of Lithuania and Germany relationship. - Liekis, Šarūnas (Genocidas ir rezistencija, 2004)
This article present document found in archive in USA. It is a the plan of Nazi German military operation named Flottenparade (Vessel parade). According this plan, if Poland have started military actions against Lithuania, Germany would have occupied Klaipėda. This document reveals details of the plans, also describes atmosphere of these days, Lithuanian army situation and potential.